In Vivo Optical Imaging of Neurogenesis: Watching New Neurons in the Intact Brain - Sebastien Couillard-Despres; Rudolf Finkl; Beate Winner; Sonja Ploetz; Dirk Wiedermann; Robert Aigner; Ulrich Bogdahn; Juergen Winkler; Mathias Hoehn; Ludwig Aigner (Molecular Imaging)
Adult neurogenesis is a highly dynamic process modulated by several pathologic and environmental factors, as well as by various compounds. So far, available techniques to study neurogenesis are lengthy and personnel and cost intensive. We developed a new tool based on the doublecortin promoter driving the expression of the luciferase reporter gene (DCX-promo-luciferase) in transgenic mice to perform in vivo imaging of neurogenesis. Indeed, the DCX-promo-luciferase mice allowed optical in vivo imaging of the onset of and increase in neurogenesis in developing fetal brains, as well as imaging of neurogenesis in the intact adult mouse central nervous system. Moreover, the capacity to specifically detect a small number of migrating neuronal precursors in vivo after transplantation is for the first time feasible using this DCX-promo-luciferase transgenic tool. The present imaging approach offers several crucial advantages over methods currently available, such as bromodeoxyuridine incorporation or labeling using iron oxide nanoparticles. Hence, it allows longitudinal study of neurogenesis in intact animals without the requirement of cellular prelabeling. Moreover, it guarantees that detection is specific for neuronal precursors and restricted to viable cells. Hence, our DCX-promo-luciferase transgenic model constitutes an effective tool that answers the pressing need for rapid investigation of the impact on neurogenesis of a large number of candidate compounds waiting to be tested.